MODEL TABUNGAN RUMAH TANGGA (Kajian Literatur) - Efriyani Sumastuti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
Household saving, as a part of social saving, is one of the sources of fund for investment and development. It means it is necessary to organize what so called saving mobilization to push investment and to ensure the development program. Meanwhile, the model and behavior towards household saving always change from time to time due to varied and complex determining factors. Therefore, the household saving model should be conducted for policy analyzis. Household saving model could be derived from Classic, Keynes, Life Cycle Hypothesis (LCH), Permanent Income Hypothesis (PIH), Relative Income Hypothesis (RIH), Overlapping Generation Model (OLG), Rational Expectation (Ratex) and Life Cycle-Permanent Income Hypothesis (LC-PIH). The purpose of this article is to review the theoretical literature and empirical result on the household saving model.